Misi Gereja dalam Membebaskan Pria Feminin dari Diskriminasi Akibat Paham Toxic Masculinity - Fernando Dapot Hamonangan L. Tobing; Delinda Elizabeth Aritonang (Program Pascasarjana UKIM, 2024)
Society has a growing view of how men and women act in their daily lives. However, some men or women act not according to these standards and many of them experience acts of discrimination. The discrimination received by the victims is also not only limited to verbal discrimination, many also receive physical discrimination, so many victims are psychologically disturbed, even to the point of experiencing physical injuries. For this reason, the author here focuses more on discrimination against feminine men and tries to make readers aware that this standard cannot be used as a reference to classify a person's gender and is not a reason for someone to be free to discriminate. The author's reason for focusing more on discrimination that occurs in feminine men is because it is feminine men who often receive this discrimination. In fact, because of the many cases that occurred, the term Toxic Masculinity emerged, which is an understanding of actions that do not accept the nature of men who do not act according to the standards developed in society and are also one of the causes of discrimination against feminine men. The author uses an analytical method in this writing, namely by doing a comparison between men who are categorized as normal and feminine, looking for the contrast, and the causes, and showing the response of the two types of men.